2022
DOI: 10.3390/metabo12070578
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Deuterium-Labeled Armodafinil by Hydrogen–Deuterium Exchange and Its Application in Quantitative Analysis by LC-MS

Abstract: Armodafinil, the R enantiomer of modafinil, was approved in 2007 by the US Food and Drug Administration as a wake-promoting agent for excessive sleepiness treatment. Due to its abuse by students and athletes, there is a need of its quantification. Quantitative analysis by liquid chromatography-mass spectrometry, however, though very common and sensitive, frequently cannot be performed without isotopically labeled standards which usually have to be specially synthesized. Here we reported our investigation on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…Another nootropic drug, which can be detected from saliva, is armodafinil. Grocholska et al [ 75 , 76 ] demonstrated the possibility of the preparation of a deuterated armodafinil standard via a base-catalysed hydrogen–deuterium exchange (HDX) at the carbon atom and the applicability of the obtained standard in the quantitative analysis of armodafinil in human urine samples by LC-MS ( Figure 3 ). This method can be successfully used for saliva samples.…”
Section: Introductionmentioning
confidence: 99%
“…Another nootropic drug, which can be detected from saliva, is armodafinil. Grocholska et al [ 75 , 76 ] demonstrated the possibility of the preparation of a deuterated armodafinil standard via a base-catalysed hydrogen–deuterium exchange (HDX) at the carbon atom and the applicability of the obtained standard in the quantitative analysis of armodafinil in human urine samples by LC-MS ( Figure 3 ). This method can be successfully used for saliva samples.…”
Section: Introductionmentioning
confidence: 99%